Mitigation of Inrush Current in Three Phase Power Transformer by Pre-fluxing Technique - et al., Pradeep J.Kotak (International Journal of Advanced Science and Technology, 2019)
Transformers are major component for electrical energy transfer in power system. Stability and security of the transformer protection are important to system operation. At the time of transformer energization, a high current will be drawn by the transformer. The mentioned current is called transient inrush current and it may rise to ten times the nominal full load current of transformer during operation. Energization transients can produce mechanical stress to the transformer, cause protection system malfunction and it often affects the power system quality and may disrupt the operation of sensitive electrical loads such as computers and medical equipment connected to the system. Reduction and the way to control of energization transient currents have become important concerns to the power industry for engineers. One of the methods to reduce inrush current is use of point on wave switching at the time transformer is initially connected to supply. It is called controlled switching or point-on-wave switching. In the point on wave switching, the energization of three phases is controlled according to the residual flux which remains in the transformer. Conventionally, controlled switching or point on wave switching was the method being used to counter this problem, but this method required the knowledge of residual fluxes of transformer before energization which is quite tedious to get. So a technique has been proposed to mitigate inrush current in three phase transformer, by a process called pre-fluxing. After setting the initial fluxes of transformer it is energized by conventional controlled switching. A system of power transformer of specified rating is simulated in MATLAB simulink and results were obtained. This Paper describes the modeling of inrush current of 3- phase, 300 MVA, 11/400 KV, 50 Hz transformer, and mitigation of inrush current with both techniques using point on wave switching and prefluxing. The simulation is done in MATLAB.